Broad repetitive transcranial magnetic stimulation (rTMS) of the precuneus in Alzheimer's disease: A rationale and study design - Michael K. Leuchter; Hanadi A. Oughli; Kelly A. Durbin; Nicholas J. Jackson; David Elashoff; Timothy S. Chang; Juliana Corlier; Doan Ngo; Cole Matthews; Darice Wong; Brent L. Fogel; Gal Bitan; et al. (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract INTRODUCTION Brain network dysfunction, particularly within the default mode network (DMN), is an increasingly apparent contributor to the clinical progression of Alzheimer's disease (AD). Repetitive transcranial magnetic stimulation (rTMS) can target key DMN hubs, maintain signaling function, and delay or improve clinical outcomes in AD. Here, we present the rationale and design of a study using off‐the‐shelf equipment and the latest clinical evidence to expand on prior rTMS work and reduce participant burden in the process. METHODS We will conduct a two‐stage trial of large‐coil rTMS targeting the precuneus (a key hub in the DMN affected by AD) in 54 participants with mild to moderate Alzheimer's Clinical Syndrome focused primarily on determining tolerability and feasibility and secondarily focused on determining short‐term efficacy for memory. The first stage will involve 5 to 10 participants receiving open‐label active treatment to refine the protocol. The following second stage will consist of a 1:1 randomized, double‐blind, sham‐controlled clinical trial to study feasibility and tolerability while exploring target engagement and short‐term efficacy for memory. Participants will undergo 16 total rTMS brain stimulation sessions over the course of 5 weeks. A full course of open‐label active treatment will be offered as an extension to the sham group after unblinding. Outcomes will focus on completion rates and adverse events to demonstrate feasibility and tolerability. Further exploratory outcomes will include neuropsychological assessments, electroencephalography, neuroimaging, and blood biomarkers to demonstrate the feasibility of collection and explore preliminary changes in these measures. RESULTS We anticipate this treatment is feasible and tolerable and may show evidence of target engagement and clinical improvement. DISCUSSION Should we achieve expected positive outcomes in feasibility and tolerability, this will justify future work focusing on clear demonstrations of clinical efficacy and biomarker engagement, as well as enhancement of generalizability and scalability. Highlights Induction‐to‐maintenance repetitive transcranial magnetic stimulation (rTMS) of the precuneus is a promising treatment for Alzheimer's disease (AD), though recent methods require intensive personalization. We propose here a trial design of precuneus rTMS in mild‐to‐early‐moderate AD dementia using exclusively off‐the‐shelf equipment and protocol modifications to reduce participant burden. Our two novel modifications from prior work are (1) using a larger rTMS coil, and (2) consolidating the induction phase of treatment. This trial focuses primarily on tolerability and feasibility while exploring clinical measures of efficacy and biomarkers of target engagement. Our trial is registered at ClinicalTrials.gov NCT06597942.